Main immunological hypotheses of the canine demodicosis - Cen-Cen, Carlos Josué; Bolio-González, Manuel Emilio; Rodríguez-Vivas, Roger Iván (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Canine demodicosis is a common cutaneous condition in dogs, characterized by a proliferative increase of mites from the genus Demodex. Despite its high prevalence, the onset and development of demodicosis are still unknown; however, they are primarily associated to an immune dysfunction. The immune system plays an important role controlling mites in healthy animals as well as on the development of the disease in sick animals. The immune mechanisms that lead to an unbalance in the innate and adaptive systems, as well as the mite mechanisms to evade the immune system remain unknown. Consequently, various hypotheses have been proposed to try explaining possible immune mechanisms. This paper aims to conduct an updated review of the main hypotheses related to the immune mechanisms associated to demodicosis in dogs.